Development of organic nutrients management system for profitable and soil-supportive French bean (Phaseolus vulgaris L.) farming in North Eastern Himalayas, India - Singh, Raghavendra; Kumar, Amit; Babu, Subhash; Avasthe, Ravikant; Das, Anup; Rathore, Sanjay Singh; Kumar, Sanjeev; Singh, Chandu; Sharma, Vikas; Bhupenchandra, Ingudam (Frontiers in Sustainable Food Systems, 2023)
French bean (Phaseolus vulgaris L.) cultivation faces multipronged challenges of low farm productivity, poor economic returns, and soil health deterioration in the hilly ecosystem of India. Hence, the development of a cost-effective and soil-supportive French bean cultivation technology is highly warranted. Thus, a field experiment was conducted for two consecutive seasons in the Sikkim region of the Indian Himalayas to assess the impact of different organic nutrient sources on the production potential, profitability, and soil health of French bean. Eight organic nutrient management practices viz. Farmers' practice, 100% recommended dose of nitrogen (RDN) through FYM, 100% RDN through mixed compost (MC), 100% RDN through vermicompost (VC), 50% RDN through FYM + 50% RDN through MC, 50% RDN through FYM + 50% RDN through VC, 50% RDN through MC + 50% RDN through VC, 33% RDN through FYM + 33% RDN through MC+ 33% RDN through VC were assigned in three times replicated randomized complete block design. Results revealed that supply of 33% RDN through FYM + 33% RDN through MC+ 33% RDN through VC 33%, recorded the highest pod yield (8.30 and 8.00 Mg ha-1), and net returns (1831 and 1718 US ha-1). Furthermore, the supply of 33% RDN through FYM + 33% RDN through MC+ 33% RDN through VC 33% also had a positive impact on soil health. Equal supply of RDN through FYM+ MC+ VC increases soil pH by 8.35%, SOC by 5.45%, available N by 6.32%, available P by 16%, available K by 9.92%, and micronutrients by 5-7% over farmers' practice. Thus, the supply of RDN through the integration of FYM + MC + VC is an economically robust and soil-supportive practice for organic French bean production in the hilly ecosystem of North East India.